'Airport People' in Transformation: Vertical Disintegration and the Reconfiguration of Occupational Belonging in Terminal Work at Helsinki-Vantaa International Airport. (March 2021) - Vieno, Atte
This article examines the effects of the vertical disintegration of production on airport terminal workers through the theoretical lens of occupational belonging, highlighting themes of sensory and embodied experience, changing dynamics of employment relationships, and new patterns of inclusion and exclusion. The article contributes to efforts to produce nuanced empirical accounts of the dynamics of post-Fordist work, showing how restructuring had the effect of disrupting employment relations and activity rhythms, while nevertheless preserving 'the airport' as a symbolic and relational setting in relation to which occupational belonging could be constructed. The article examines how the work of binding people and jobs, previously undertaken by integrated organisations, was taken up by workers themselves through their personal relationships and will to belong. The article highlights the capacity to undertake this work of belonging as a central dynamic of occupational inclusion and exclusion, a capacity which in this empirical context was experienced as being shaped by age and the ability to make use of personal relationships in navigating precarious employment relations. Based on this empirical analysis, the article argues for belonging as a valuable perspective for studies of materiality, symbolic identification and relationality in post-Fordist work.